2008
DOI: 10.1002/hep.22498
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of iron from lysosomes into mitochondria is a key event during oxidative stress-induced hepatocellular injury

Abstract: Iron overload exacerbates various liver diseases. In hepatocytes, a portion of non-heme iron is sequestered in lysosomes and endosomes. The precise mechanisms by which lysosomal iron participates in hepatocellular injury remain uncertain. Here, our aim was to determine the role of intracellular movement of chelatable iron in oxidative stress-induced killing to cultured hepatocytes from C3Heb mice and Sprague-Dawley rats. Mitochondrial polarization and chelatable iron were visualized by confocal microscopy of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
122
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(131 citation statements)
references
References 55 publications
9
122
0
Order By: Relevance
“…However, Schisandra chinensis may be able to treat acute liver injury though protection of the mitochondria. Disruption of lysosomes in hepatocytes following acetaminophen treatment has been observed in previous studies (13,15). Notably, Schisandra chinensis was also found to protect lysosomes in the present study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, Schisandra chinensis may be able to treat acute liver injury though protection of the mitochondria. Disruption of lysosomes in hepatocytes following acetaminophen treatment has been observed in previous studies (13,15). Notably, Schisandra chinensis was also found to protect lysosomes in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…Studies have indicated that lysosomal disruption occurs subsequent to numerous types of cellular stresses in hepatocytes and other cell types (11)(12)(13). A breakdown of lysosomes may result in cell death by necrosis, which is associated with an increase in cytosolic acidification (14).…”
Section: Introductionmentioning
confidence: 99%
“…A striking feature of necrotic hepatocytes from Nrf2 -/-mice fed iron-rich diet was the extreme swelling of mitochondria. In hepatocytes, non-heme iron that is initially sequestered in lysosomes may be released and taken up into mitochondria, where it catalyzes toxic ROS-mediated reactions [31]. This may open nonspecific permeability transition pores in the mitochondrial inner membrane that cause mitochondrial membrane depolarization, uncoupling of oxidative phosphorylation, and large scale mitochondrial swelling, leading to hepatocyte necrosis from Version: Postprint (identical content as published paper) This is a self-archived document from i3S -Instituto de Investigação e Inovação em Saúde in the University of Porto Open Repository For Open Access to more of our publications, please visit http://repositorio-aberto.up.pt/ A01/00 adenosine triphosphate depletion.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocyte Isolation and Culture-Hepatocytes were isolated from 200-to 250-g overnight-fasted male Sprague-Dawley rats (Charles River Laboratories, Inc., Wilmington, MA) by collagenase perfusion as described previously (33,34). Hepatocytes were resuspended in Waymouth's MB-752/1 growth medium (Invitrogen) supplemented with 10% fetal bovine serum, 100 nM insulin (Squibb-Novo, Princeton, NJ), 100 nM dexamethasone (LyphoMed, Rosemont, IL), 100 units/ml penicillin, and 100 g/ml streptomycin.…”
Section: Methodsmentioning
confidence: 99%